IMPLEMENTASI PRINSIP HUKUM EKONOMI SYARI’AH DALAM PEMBIAYAAN MIKRO SYARI’AH STUDI KASUS PADA BMT MUAMALAH SYARI’AH TEBUIRENG JOMBANG - Resika Triani Putri; Syaiin Syaiin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the implementation of sharia economic law principles in sharia microfinance with a case study at BMT Muamalah Syariah Tebuireng Jombang. Sharia Microfinance Institutions such as BMT have an important role in supporting the people's economy, especially for small communities who need access to sharia-based finance. This study aims to analyze how the principles of sharia economic law are applied in microfinance at BMT Muamalah Syariah Tebuireng and its implications for customers. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that BMT Muamalah Syariah Tebuireng applies various sharia contracts in microfinance, such as murabahah, mudharabah, and hiwalah. The implementation of sharia principles in microfinance at this BMT is in accordance with sharia economic law, marked by the prohibition of usury, the application of a profit-sharing system, and transparency in every transaction. However, this study also found several challenges, such as the lack of customer understanding of sharia contracts and limitations in supervising sharia compliance.